The Influence of Corporate Social Responsibility on the Attractiveness of Employers in the Perception of Generation Z - Maj, Jolanta; Kasperek, Natalia (Contemporary organisation and management. Challenges and trends, 2020)
Corporate Social Responsibility has become an important instrument in the development of an employer’s branding strategy. Research shows that Generation Y is highly sensitive in regards to CSR issues, and that CSR influences their perception of an employer’s attractiveness. However, the question this paper aims to find an answer to is whether this would also apply to the next generation, Generation Z. For this purpose, we conducted a survey (n = 250) with a sample of representatives of Generation Z. The findings suggest that Generation Z perceives CSR as an important factor in their choice of employer, however not important enough to convince them to reject a job offer if the employer is not perceived as ethical and responsible.